The little mermaid - King, Enid C (London : Lady Bird Ltd)
The story of "The Little Mermaid" by Andersen unfolds in a vividly imagined undersea kingdom where the sea king, a widower, lives with his elderly mother and six mermaid daughters. Each daughter has her own unique garden, and the youngest cherishes her garden filled with rose-red blooms and a striking marble statue of a boy from a sunken ship. The tale captivates with its richly detailed setting, drawing readers into the enchanting aquatic world. The Allure of the Surface Intrigued by the stories of the world above, shared by their father and grandmother, the mermaid sisters eagerly anticipate their fifteenth birthdays. Reaching this milestone allows each to venture to the surface and explore. The sisters return with enchanting tales$1 (Bone is startled by a small dog, another drifts on an iceberg, while a third frolics with dolphins and whales. These magical accounts fuel the youngest sister's anticipation as she finally makes her own journey to the surface. An Unforgettable Encounter On her first visit above, the youngest mermaid spies a majestic, three-masted ship where a prince's sixteenth birthday celebration is underway. The sight of the handsome prince captivates her heart. But as a violent storm wrecks the ship, the prince is left unconscious, and the young mermaid rescues him, guiding him to safety. She keeps her daring act a secret from her family, silently treasuring her love for the prince. A Silent Sacrifice Eventually, she confides in her sisters, who point out the prince's palace to her. Gazing at it longingly each evening, she learns from her grandmother that humans have a shorter life span than merfolk, but they are blessed with eternal souls. Consumed by love and the desire for a soul, she seeks the help of a sea witch, willing to pay the high price of her voice for a chance at humanity. The Witch's Bargain In a cruel exchange, the sea witch cuts out the young mermaid's tongue, rendering her mute. She drinks a potion that transforms her tail into legs, with the condition that if the prince marries her, she will gain a soul; if he marries another, she will dissolve into sea foam. The stakes are heartbreakingly high, yet the mermaid takes the risk for love. The Heart's Dilemma The prince grows fond of the voiceless mermaid, charmed by her presence, yet he does not consider her for his bride. His heart belongs to another, and he marries this other woman. On the night of his wedding, the mermaid's sisters emerge from the sea, bringing a knife from the witch, a desperate offer to save their sister. But the mermaid cannot bring herself to harm the prince and instead chooses self-sacrifice. A Transformative Resolution In a poignant moment of surrender, she throws herself into the sea, ready to become foam. Yet, she is lifted by the daughters of the air, ethereal beings who tell her that they earn immortal souls through good deeds. Welcomed into their ranks, the little mermaid's journey continues beyond the confines of the sea, offering a bittersweet sense of redemption. Andersen's Intent and Legacy Upon publication, some believed the ending was contrived, yet Andersen himself insisted it was intentional, reflecting in a letter that he always meant for the story to conclude this way. The original title "Daughters of the Air" suggests Andersen's nuanced views on religion and redemption, offering the mermaid a chance for an immortal soul through virtue. Much like the little mermaid, Andersen might have seen a part of himself in the story, navigating unrequited love. A Lasting Symbol The enduring legacy of the tale is commemorated by the famous bronze statue of the Little Mermaid by Edvard Eriksen, installed in 1913 on the harbor promenade of Copenhagen. This statue stands as a testament to the story's timeless appeal, capturing the hearts and imaginations of many across the globe.s
Fiction English book
Keywords: English - Fiction book